Salt-spray-corrosion-resistant and marine-environment-resistant offshore photovoltaic glass
By applying a multifunctional coating structure on offshore photovoltaic glass, including high corrosion resistance, bioadhesion and superhydrophobic coating, the corrosion, bioadhesion and water droplet adhesion problems that are prone to occur in high salt spray, high humidity and strong ultraviolet environments, significantly improving the durability and performance of the glass, extending its service life and reducing maintenance costs.
Patent Information
- Application Number
- CN202411961680.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
Photovoltaic glasses of offshore photovoltaic power plants are prone to salt spray corrosion, biological adhesion and water droplet adhesion problems in high salt spray, high humidity and strong ultraviolet environments, resulting in reduced performance and shortened service life.
It adopts a multifunctional coating structure, including a high corrosion resistance coating, a bioadhesive coating and a superhydrophobic coating, consisting of cerium oxide and zinc oxide, copper and silver ions, fluoride or silane compounds, respectively, and is uniformly coated on the surface of the photovoltaic glass by spraying or dip coating and curing.
It significantly improves the salt spray corrosion resistance, bioadhesion resistance and self-cleaning function of offshore photovoltaic glass, extends the service life of the photovoltaic system, reduces maintenance costs, and maintains stable photoelectric conversion efficiency.
Smart Images

Figure HDA0005217320630000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of photovoltaic glass, and in particular to a marine photovoltaic glass that is resistant to salt spray corrosion and marine environment. Background Art
[0002] Offshore photovoltaic power stations are usually exposed to environmental conditions such as high salt fog, high humidity and strong ultraviolet rays. The performance and service life of photovoltaic glass are significantly reduced due to the long-term influence of these factors. Traditional photovoltaic glass has poor corrosion resistance and self-cleaning ability in offshore environments, resulting in reduced efficiency of photovoltaic cells and even problems such as breakage and aging, which not only increases maintenance costs, but also seriously affects the operating efficiency and economic benefits of the power station.
[0003] There are still the following problems in the daily use of offshore photovoltaics:
[0004] 1. Salt spray corrosion problem: Salt spray in seawater is one of the main causes of corrosion and damage to the surface of photovoltaic glass. When photovoltaic glass is exposed to a high salt spray environment, salt easily accumulates on the surface of the glass, and then reacts with ultraviolet rays and moisture to cause gradual corrosion of the glass surface, reducing light transmittance, affecting photoelectric conversion efficiency, and shortening the service life of photovoltaic cells.
[0005] 2. Biological attachment problem: In the marine environment, it is common for microorganisms and algae to attach and grow on the surface of photovoltaic glass. Biological attachment not only makes the glass surface dirty, but also forms biofilm, which further affects the light transmittance of photovoltaic glass and hinders the effective absorption of sunlight, thereby reducing the photoelectric conversion efficiency. In addition, the accumulation of biofilm may also cause corrosion, increasing the maintenance frequency and cost of glass.
[0006] 3. Water droplet adhesion problem: In the marine environment, rainwater and seawater easily accumulate on the surface of photovoltaic glass. The presence of water droplets will cause salt residue, further aggravating corrosion. At the same time, water droplets staying on the glass surface for a long time may also cause dirt to adhere, affecting the light transmittance and self-cleaning ability of photovoltaic glass. The surface of traditional photovoltaic glass lacks effective waterproof and self-cleaning functions, which increases the difficulty of cleaning and maintenance.
[0007] To address these issues, traditional photovoltaic glass mostly uses a single anti-corrosion or anti-fouling coating, but this method often cannot solve the above-mentioned multiple problems at the same time. Therefore, there is an urgent need for a multifunctional coating technology that can integrate anti-corrosion, anti-biological attachment and super-hydrophobic functions to improve the durability and performance of photovoltaic glass in the marine environment and extend the service life of photovoltaic power stations. Summary of the invention
[0008] In order to overcome the above-mentioned defects of the prior art, the present invention provides a marine photovoltaic glass that is resistant to salt spray corrosion and marine environment to solve the problems raised in the background technology.
[0009] In order to achieve the above-mentioned purpose of the invention, the present invention provides an offshore photovoltaic glass that is resistant to salt spray corrosion and marine environment. The offshore photovoltaic glass includes a photovoltaic glass body, a high corrosion-resistant coating, an anti-biological attachment coating and a super-hydrophobic coating. The high corrosion-resistant coating is arranged on the photovoltaic glass body, the anti-biological attachment coating is coated on the high corrosion-resistant coating, the super-hydrophobic coating is coated on the anti-biological attachment coating, and the high corrosion-resistant coating includes cerium oxide and zinc oxide.
[0010] Furthermore, the preparation method of the highly corrosion-resistant coating comprises:
[0011] Raw material preparation:
[0012] The raw materials include cerium oxide and zinc oxide. These materials have excellent corrosion resistance and show strong resistance to salt spray corrosion in seawater environments. Cerium oxide can enhance its bonding with the glass surface by changing its surface oxidation state. Zinc oxide has good chemical stability, which helps prevent corrosive substances from corroding photovoltaic glass.
[0013] Use ethanol or acetone as a solvent to help the coating be evenly distributed on the glass surface, ensuring the leveling and adhesion of the coating; surfactants are used to enhance the adhesion of the coating to the glass surface and optimize the fluidity and uniformity of the coating;
[0014] Preparation of highly corrosion resistant coatings:
[0015] Cerium oxide and zinc oxide are mixed in a ratio of 2:1, and ethanol is used as a solvent to dissolve them into a solution of a certain concentration;
[0016] Use spraying or dipping to evenly apply the solution on the cleaned photovoltaic glass surface. After coating, use air drying or slight heating to cure the coating.
[0017] Furthermore, the method for preparing the anti-biological attachment coating comprises:
[0018] Raw material preparation:
[0019] Copper ions and silver ions are used as the core components of the anti-biological adhesion coating. Copper and silver have natural antimicrobial properties, which can inhibit the adhesion of marine microorganisms and algae, and keep the surface of photovoltaic glass clean. Copper and silver ions are gradually released through chemical reactions, effectively preventing the formation of biofilm for a long time;
[0020] Dissolve copper ions or silver ions in deionized water at a concentration of 0.1 M;
[0021] After the anti-corrosion coating is cured, a solution containing copper or silver ions is evenly coated on the surface of the photovoltaic glass by dipping or spraying to form a thin film, which is then left in the air until completely dry.
[0022] Furthermore, the preparation method of the super hydrophobic coating comprises:
[0023] Raw material preparation:
[0024] Fluoride or silane compounds are used. These materials can significantly enhance the hydrophobicity of the coating surface. Through chemical bonding, they form a micron or nanometer-level surface structure, which makes water droplets form a beading effect on the glass surface, thereby reducing water droplet retention and dirt adhesion.
[0025] Preparation of super hydrophobic coating:
[0026] Using ammonium fluoride or silane compounds, coating on the surface of the anti-biological adhesion coating through a diluted solution;
[0027] The super-hydrophobic coating was evenly coated on the glass surface using a spin coating method with a spin coating rate of 3000 rpm and a duration of 30 seconds.
[0028] After coating, the glass was dried at 60°C for more than 1 hour to ensure that the coating was cured and formed a stable hydrophobic surface.
[0029] Furthermore, after all coatings of the photovoltaic glass are applied, the photovoltaic glass needs to be cured. The photovoltaic glass is placed in an oven for curing. The curing temperature is set to above 70°C and the curing time is more than 2 hours to ensure that the coating is completely dry and firmly bonded to the photovoltaic glass body.
[0030] Furthermore, after the photovoltaic glass coating is cured, the photovoltaic glass needs to be subjected to a weather resistance test. The offshore photovoltaic glass is placed in a salt fog environment with a salt fog concentration of 5%. The test duration is more than 1,000 hours. The performance of the coating in the salt fog environment is recorded, and changes in the coating surface are observed using a scanning electron microscope.
[0031] Furthermore, after the photovoltaic glass is prepared, it is necessary to conduct an optical performance test. The transmittance of the photovoltaic glass is measured using a UV-visible spectrophotometer to ensure that the light transmittance is not less than 90% and remains stable. By calculating the relationship between light transmittance and surface roughness, the coating thickness and coating method are optimized to improve the photoelectric conversion efficiency.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The multifunctional coating structure of this application can significantly improve the performance and durability of offshore photovoltaic glass:
[0034] Anti-corrosion coating: improve the salt spray corrosion resistance of photovoltaic glass, reduce the erosion of seawater on glass and photovoltaic cells, and extend the service life of photovoltaic systems by 3-5 times;
[0035] Anti-biological adhesion coating: effectively inhibits the adhesion of marine microorganisms and algae, keeps the glass surface clean, and improves light transmittance and photoelectric conversion efficiency;
[0036] Super hydrophobic coating: Enhances the self-cleaning function of the glass surface, reduces maintenance costs, and reduces the decline in light transmittance by more than 50% in long-term use;
[0037] In addition, the coating of this multifunctional coating structure has good adhesion and weather resistance, and can maintain stable performance under harsh marine environmental conditions. The stability of offshore photovoltaic glass in high salt fog, high humidity and strong ultraviolet light environments is significantly better than that of traditional photovoltaic glass, providing a guarantee for the long-term and reliable operation of offshore photovoltaic power stations. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the three-dimensional structure of an embodiment of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the invention, rather than all the embodiments. The embodiments of the present invention are described below in conjunction with the drawings.
[0040] At present, photovoltaic glass in offshore photovoltaic power stations faces a variety of environmental challenges, especially salt spray corrosion, biological adhesion and dirt accumulation. In order to cope with these challenges, there are some technical solutions on the market, but most of them have the following limitations:
[0041] Anti-corrosion coating technology: Anti-corrosion coating technology on the market usually uses simple coatings or single metal oxides (such as aluminum, zinc, etc.) to improve the salt spray resistance of photovoltaic glass; however, most of these coatings cannot remain stable in long-term marine environments, especially in high humidity and high salt spray environments, which are prone to shedding, aging or performance degradation, resulting in insufficient corrosion resistance of photovoltaic glass and affecting the working efficiency and service life of photovoltaic cells;
[0042] Anti-biological attachment coating 3 technology: In terms of anti-biological attachment, the existing technology usually adopts a single chemical antifouling coating, such as coating copper or silver ions to prevent the attachment of marine microorganisms, algae, etc.; however, such coatings often lose their effectiveness in long-term use, and their protective ability may be reduced due to biological accumulation or damage to the external environment; in addition, the antibacterial coatings in the existing technology are mostly organic coatings, which are easily affected by ultraviolet rays or seawater immersion, resulting in poor stability of the coating, which reduces the service life of photovoltaic glass;
[0043] Super hydrophobic coating 4 technology: The super hydrophobic coating 4 technology on the market is mainly concentrated in the field of industrial glass and architectural glass, mainly through fluoride or silane compound coating to achieve super hydrophobic effect; the main advantage of these coatings is that they can effectively reduce the retention of water droplets on the glass surface and reduce the adhesion of dirt; however, the application effect of existing super hydrophobic coating 4 in marine environment is limited, because of its poor tolerance to salt spray, ultraviolet rays and high humidity, it is easy to have surface function failure, resulting in the inability to maintain the self-cleaning effect continuously, and it cannot cope with the harsh conditions of the marine environment for a long time;
[0044] Lack of comprehensive protection technology: Currently, the most common technologies on the market are single-function coating technologies, such as focusing only on anti-corrosion, anti-bacteria or hydrophobicity. However, facing the complex environment faced by offshore photovoltaic power stations, a single coating often cannot comprehensively solve all problems. The market still lacks a comprehensive, multifunctional coating technology that has anti-corrosion, anti-biological attachment and super-hydrophobic functions to cope with the complex challenges in the offshore environment.
[0045] In order to solve the above technical problems, the present application discloses a marine photovoltaic glass resistant to salt spray corrosion and marine environment, referring to Figure 1 , the offshore photovoltaic glass comprises a photovoltaic glass body 1, a high corrosion resistance coating 2, an anti-biological attachment coating 3 and a super hydrophobic coating 4, the high corrosion resistance coating 2 is arranged on the photovoltaic glass body 1, the anti-biological attachment coating 3 is coated on the high corrosion resistance coating 2, the super hydrophobic coating 4 is coated on the anti-biological attachment coating 3, and the high corrosion resistance coating 2 comprises cerium oxide and zinc oxide;
[0046] The preparation method of the high corrosion resistance coating 2 includes:
[0047] Raw material preparation:
[0048] The raw materials include cerium oxide and zinc oxide. These materials have excellent corrosion resistance and show strong resistance to salt spray corrosion in seawater environments. Cerium oxide can enhance its bonding with the glass surface by changing its surface oxidation state. Zinc oxide has good chemical stability, which helps prevent corrosive substances from corroding photovoltaic glass.
[0049] Use ethanol or acetone as a solvent to help the coating be evenly distributed on the glass surface, ensuring the leveling and adhesion of the coating; surfactants are used to enhance the adhesion of the coating to the glass surface and optimize the fluidity and uniformity of the coating;
[0050] Preparation of high corrosion resistance coating 2:
[0051] Cerium oxide and zinc oxide are mixed in a ratio of 2:1, and ethanol is used as a solvent to dissolve them into a solution of a certain concentration, wherein the weight concentration of the solution is 20%;
[0052] Use spraying or dipping to evenly coat the solution on the cleaned photovoltaic glass surface. After coating, use air drying or slight heating treatment at a temperature of 60°C to solidify the coating.
[0053] The preparation method of the anti-biological adhesion coating 3 comprises:
[0054] Raw material preparation:
[0055] Copper ions and silver ions are used as the core components of the anti-biological adhesion coating 3. Copper and silver have natural antimicrobial properties, which can inhibit the attachment of marine microorganisms and algae, keep the surface of photovoltaic glass clean, and the copper and silver ions are gradually released through chemical reactions, effectively preventing the formation of biofilm for a long time;
[0056] Dissolve copper ions or silver ions in deionized water at a concentration of 0.1 M;
[0057] After the anti-corrosion coating is cured, a solution containing copper or silver ions is evenly coated on the surface of the photovoltaic glass by dipping or spraying to form a thin film, which is then left in the air until completely dry.
[0058] The preparation method of the super hydrophobic coating 4 comprises:
[0059] Raw material preparation:
[0060] Fluoride or silane compounds are used. These materials can significantly enhance the hydrophobicity of the coating surface. Through chemical bonding, they form a micron or nanometer-level surface structure, which makes water droplets form a beading effect on the glass surface, thereby reducing water droplet retention and dirt adhesion.
[0061] Preparation of super hydrophobic coating 4:
[0062] ammonium fluoride or silane compound is used to coat the surface of the anti-biological attachment coating 3 through a diluted solution, and the concentration of the diluted solution is 0.5%;
[0063] The super-hydrophobic coating 4 was evenly coated on the glass surface by spin coating at a rate of 3000 rpm for 30 seconds;
[0064] After coating, the glass was dried at 60°C for more than 1 hour to ensure that the coating was cured and formed a stable hydrophobic surface;
[0065] After all coatings of the photovoltaic glass are applied, the photovoltaic glass needs to be cured. The curing process includes: placing the photovoltaic glass in an oven for curing, setting the curing temperature to above 70° C., and the curing time to above 2 hours, to ensure that the coating is completely dry and firmly bonded to the photovoltaic glass body 1;
[0066] After the photovoltaic glass coating is cured, the photovoltaic glass needs to be tested for aging and weather resistance. The offshore photovoltaic glass is placed in a salt spray environment with a salt spray concentration of 5%. The test duration is more than 1,000 hours. The performance of the coating in the salt spray environment is recorded, and the changes in the coating surface are observed through a scanning electron microscope to ensure that the anti-corrosion coating remains intact after long-term exposure.
[0067] After the photovoltaic glass is prepared, it is also necessary to conduct an optical performance test. Use a UV-visible spectrophotometer to measure the light transmittance of the photovoltaic glass to ensure that the light transmittance is not less than 90% and remains stable. By calculating the relationship between light transmittance and surface roughness, the coating thickness and coating method can be optimized to improve the photoelectric conversion efficiency.
[0068] The multifunctional coating structure of this application can significantly improve the performance and durability of offshore photovoltaic glass:
[0069] Anti-corrosion coating: Improve the salt spray corrosion resistance of photovoltaic glass, reduce the erosion of seawater on glass and photovoltaic cells, and extend the service life of the photovoltaic system by 3 to 5 times.
[0070] Anti-biological adhesion coating 3: effectively inhibits the adhesion of marine microorganisms and algae, keeps the glass surface clean, and improves light transmittance and photoelectric conversion efficiency.
[0071] Super hydrophobic coating 4: Enhances the self-cleaning function of the glass surface, reduces maintenance costs, and reduces the decrease in light transmittance by more than 50% during long-term use.
[0072] In addition, the coating of this multifunctional coating structure has good adhesion and weather resistance, and can maintain stable performance under harsh marine environmental conditions. The stability of offshore photovoltaic glass in high salt fog, high humidity and strong ultraviolet light environments is significantly better than that of traditional photovoltaic glass, providing a guarantee for the long-term and reliable operation of offshore photovoltaic power stations.
[0073] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.
Claims
1. A marine photovoltaic glass resistant to salt spray corrosion and marine environment, characterized in that: The offshore photovoltaic glass includes a photovoltaic glass body, a high corrosion-resistant coating, an anti-biological attachment coating and a super-hydrophobic coating. The high corrosion-resistant coating is arranged on the photovoltaic glass body, the anti-biological attachment coating is coated on the high corrosion-resistant coating, the super-hydrophobic coating is coated on the anti-biological attachment coating, and the high corrosion-resistant coating includes cerium oxide and zinc oxide.
2. The marine photovoltaic glass resistant to salt spray corrosion and marine environment according to claim 1, characterized in that: The preparation method of the highly corrosion-resistant coating comprises: Raw material preparation: The raw materials include cerium oxide and zinc oxide. These materials have excellent corrosion resistance and show strong resistance to salt spray corrosion in seawater environments. Cerium oxide can enhance its bonding with the glass surface by changing its surface oxidation state. Zinc oxide has good chemical stability, which helps prevent corrosive substances from corroding photovoltaic glass. Use ethanol or acetone as a solvent to help the coating be evenly distributed on the glass surface, ensuring the leveling and adhesion of the coating; surfactants are used to enhance the adhesion of the coating to the glass surface and optimize the fluidity and uniformity of the coating; Preparation of highly corrosion resistant coatings: Cerium oxide and zinc oxide are mixed in a ratio of 2:1, and ethanol is used as a solvent to dissolve them into a solution of a certain concentration; Use spraying or dipping to evenly apply the solution on the cleaned photovoltaic glass surface. After coating, use air drying or slight heating to cure the coating.
3. The marine photovoltaic glass resistant to salt spray corrosion and marine environment according to claim 1, characterized in that: The method for preparing the anti-biological attachment coating comprises: Raw material preparation: Copper ions and silver ions are used as the core components of the anti-biological adhesion coating. Copper and silver have natural antimicrobial properties, which can inhibit the adhesion of marine microorganisms and algae, and keep the surface of photovoltaic glass clean. Copper and silver ions are gradually released through chemical reactions, effectively preventing the formation of biofilm for a long time; Dissolve copper ions or silver ions in deionized water at a concentration of 0.1 M; After the anti-corrosion coating is cured, a solution containing copper or silver ions is evenly coated on the surface of the photovoltaic glass by dipping or spraying to form a thin film, which is then left in the air until completely dry.
4. The marine photovoltaic glass resistant to salt spray corrosion and marine environment according to claim 1, characterized in that: The preparation method of the super hydrophobic coating comprises: Raw material preparation: Fluoride or silane compounds are used. These materials can significantly enhance the hydrophobicity of the coating surface. Through chemical bonding, they form a micron or nanometer-level surface structure, which makes water droplets form a beading effect on the glass surface, thereby reducing water droplet retention and dirt adhesion. Preparation of super hydrophobic coating: Using ammonium fluoride or silane compounds, coating on the surface of the anti-biological adhesion coating through a diluted solution; The super-hydrophobic coating was evenly coated on the glass surface using a spin coating method at a rate of 3000 rpm for 30 seconds. After coating, the glass was dried at 60°C for more than 1 hour to ensure that the coating was cured and formed a stable hydrophobic surface.
5. The marine photovoltaic glass resistant to salt spray corrosion and marine environment according to claim 1, characterized in that: After all coatings of the photovoltaic glass are applied, the photovoltaic glass needs to be cured. The photovoltaic glass is placed in an oven for curing. The curing temperature is set to above 70°C and the curing time is more than 2 hours to ensure that the coating is completely dry and firmly bonded to the photovoltaic glass body.
6. The marine photovoltaic glass resistant to salt spray corrosion and marine environment according to claim 5, characterized in that: After the photovoltaic glass coating is cured, the photovoltaic glass needs to be subjected to a weather resistance test. The offshore photovoltaic glass is placed in a salt spray environment with a salt spray concentration of 5%. The test lasts for more than 1,000 hours. The performance of the coating in the salt spray environment is recorded, and changes in the coating surface are observed using a scanning electron microscope.
7. The marine photovoltaic glass resistant to salt spray corrosion and marine environment according to claim 1, characterized in that: After the photovoltaic glass is prepared, it is also necessary to conduct an optical performance test. The transmittance of the photovoltaic glass is measured using a UV-visible spectrophotometer to ensure that the light transmittance is not less than 90% and remains stable. By calculating the relationship between light transmittance and surface roughness, the coating thickness and coating method are optimized to improve the photoelectric conversion efficiency.